The Concept Learning Science Skills in Kindergarten Age Children - Ashar, Ashar; Idamayanti, Reski (PT ARRUS Intelektual Indonesia, 2023)
literature or other sources that are relevant to the research objectives. The results of the concept of learning science skills in kindergarten-aged children involve an active, explorative, and discovery-based approach. Several important concepts that can be applied to learning science skills, including inquiry (invention) approaches, problem-based learning, collaborative learning, observation and experimentation, critical thinking skills, communication and representation concepts, learning concepts related to everyday life. Learning science skills in kindergarten provides a solid foundation for children to understand science concepts, such as developing observing skills, comparing skills, classifying skills, measuring skills, communicating skills, asking questions, experimenting skills